Romiette and Julio - Draper, Sharon M. (Sharon Mills) (New York : Atheneum Books for Young Readers, 1999)
Romiette, an African-American girl, and Julio, a Hispanic boy, discover that they attend the same high school after falling in love on the Internet, but are harassed by a gang whose members object to their interracial dating.
Book Links (A.L.A.)
Books for the Teen Age (NYPL)
School Library Journal
Young Adult.
Young Adult
Keywords: African Americans -- Fiction; Gangs -- Fiction; High schools -- Fiction; Hispanic Americans -- Fiction; Internet -- Fiction; Interracial dating -- Fiction; Schools -- Fiction; African Americans -- Fiction; Gangs -- Fiction; Hispanic Americans -- Fiction; Internet -- Fiction; Interracial dating -- Fiction; School stories